THE IMMORTAL POETRY - Samatova Gulbonu daughter of Ibrahim (Journals Park Publishing, 2024)
This is the land of poets, Uzbekistan. Uzbek poet Abdulla Oripov is a man. If poetry were a garden, Abdulla Oripov would be the most plentiful and cherished fruit due to his deep insights, exceptional skills, and insatiable aptitude. They read our poet's poems with great interest, from poetry enthusiasts to regular folks who have no knowledge of poetry. What's the deal with this? The poet uses straightforward language that is easy to understand, fluid, and universally impactful. This is the reason behind this. The fight of the Uzbek people for independence, fanaticism, and national regeneration is greatly aided by the poetry of Abdulla Oripov. Thus, as we commemorate our seventh year of freedom, He received the title of "Hero of Uzbekistan" among the first people. This article also discusses a lovely incidence with a poem written by a poet in praise of a similar nation.
Keywords: Article, poet, creativity, incomparable poems.